(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile delinquency is one of the greatest problems in our society today. There are primary reasons why young people start to rebel at a young age, and that sometimes puts them in serious situations. The behavior of a child is first developed at home. So, what they first adopt at home is what they will show and apply to the community. The reintegration of juvenile delinquents into the community promotes accepting the child back into the community after being sent to youth centers and detention centers to rehabilitate and go through counseling services. The juvenile delinquents are taking a step to demonstrate to the community that they are capable of changing their undesirable behavior into something positive and socially acceptable. The researchers conclude that in order to avoid or lessen the increase in the population of juvenile delinquents and the discrimination by the community, it is necessary to conduct seminars and programs in every barangay that focus on the topic of juvenile delinquency and its effects that will benefit not only the youth but also their families and the community.